Dolores Claiborne [videorecording (DVD)] - Hackford, Taylor, 1944-; Plummer, Christopher; Bates, Kathy, 1948-; Leigh, Jennifer Jason, 1962-; Strathairn, David; King, Stephen, 1947- (Warner Home Video, 1999)
Eighteen years ago the town accused Dolores Claiborne of murdering her husband in cold blood. Now a woman lies dead and a witness finds Dolores standing over the body. Her daughter is the only one who can save her life and the only thing that stands between guilt and innocence is the evil secret that made the daughter run away ten years ago.